Peningkatan Kualitas Pembelajaran Melalui Implementasi Model Problem Based Learning Materi Interaksi Sosial - Larasati, Andi (Inovasi: Jurnal Diklat Keagamaan, 2020)
This study aims to improve the learning outcomes of Social Sciences (IPS) through a problem based learningmodel of class VIII A of SMP Negeri 2 Jatirejo, Mojokerto Regency. This type of research is a classroomaction research model by Kemmis and Mc.Taggart. This research was conducted in two cycles. Each cycleconsists of planning, implementing, observing and reflecting. The subjects in this study were students ofclass VIII A of SMP Negeri 2 Jatirejo, District of Mojokerto, totaling 28 students. Data collection methods inthis study through observation and learning outcomes tests. The research instrument used in the form ofobservation sheets and test questions. The data analysis technique used is qualitative and quantitativedescriptive data analysis. Data related to observation were analyzed qualitatively while data from test resultswere analyzed quantitatively in percentage. The results of this study indicate that by using the model ofproblem based learning the learning outcomes of social interaction material for class VIII A students of SMPNegeri 2 Jatirejo have increased and achieving the specified indicators of success that is 7.0. Masterylearning outcomes in the second cycle reached 91.18% up from 79.41% in the first cycle. The observationof the implementation of the lesson plan shows that learning is very effective with an average score of 3.33(good) in the first cycle rising to 3.73 (very good) in the second cycle. Students are very enthusiastic aboutlearning. This is based on observations of student activity with the percentage of activeness reaching87.50% (active) up in the second cycle to 95.56% (very active). Responses to the student response questionnairealso showed positive responses.